Relationship between different sources of non-protein nitrogen and supplementation times on performance and metabolism of grazing Nellore cattle during the dry season - Mota, Verônica A. C. [UNESP]; Prados, Laura F.; Nascimento, Keuven S. [UNESP]; Fernandes, Rodolfo. M. [UNESP]; Silva, Luiz F. Costa e; Holder, Vaughn B.; Pettigrew, James E.; Resende, Flávio D. [UNESP]; Siqueira, Gustavo R. [UNESP] (Springer Nature, 2022)
Two experiments were conducted to evaluate the effect of supplementation with two sources of non-protein nitrogen at different feeding times on the performance, ingestive behavior, and rumen metabolism of growing Nellore bulls during the dry season. Exp. 1: One hundred and twenty Nellore bulls, weighing 206 ± 39 kg of initial body weight (BW) and 12 months of age, were divided into 20 paddocks, and they were used in randomized block design in a 2 × 2 factorial arrangement to evaluate performance and ingestive behavior. Exp. 2: 12 rumen cannulated animals with 509 ± 59 BW, divided into 4 paddocks, were used in a triple Latin square 4 × 4 in a 2 × 2 factorial arrangement to evaluate metabolism. The factors were 2 non-protein nitrogen sources (urea or slow-release urea) and 2 feeding times (07:00 or 13:00 at 4 g/kg BW of supplement). There was no influence of non-protein sources, supplementation time, or their interaction on the grazing time or the trough time during daytime, nighttime, or total (P ≥ 0.16). There were no interactions or factor effects on ADG (P ≥ 0.45) or final body weight (P ≥ 0.39). There was an interaction between supplementation time and collection time (P < 0.01) on ruminal pH. Animals supplemented in the morning had greater total SCFA at 18 h after supplementation (P = 0.03). The supplementation time and the non-protein nitrogen sources did not alter the ingestive behavior or animal performance of young Nellore cattle.
Keywords: Coating materials; Growing phase; Nitrogen metabolism; Rumen degradable protein; Slow-release urea